The Sea and the Second World War : Maritime Aspects of a Global Conflict - Patalano, Alessio; Faulkner, Marcus (Book collections on Project MUSE., 2019)
The sea shaped the course and conduct of World War II, from the first moments of the German invasion of Poland on September 1, 1939, to the Japanese surrender on September 2, 1945. The impact could be felt far beyond the shoreline, as the arms and armies carried across the oceans were ultimately destined to wage war ashore. Populations and industries depended on the raw materials and supplies in a war that increasingly became a contest of national will and economic might. Ultimately, it was the war at sea that linked numerous regional conflicts and theaters of operation into a global war.As the war grew in complexity and covered an increasingly larger geographical area, the organization of the maritime effort and the impact it had on the formulation of national strategy also evolved. This volume illustrates the impact of naval operations on the Second World War by highlighting topics previously neglected in the scholarship. In doing so, it provides new insights into political, strategic, administrative, and operational aspects of the maritime dimension of the war.